Improving Students' Time Management And Problem Solving Abilities Through Creative Problem Solving Based Learning In Smpn 1 Pangkatan Students - Aulia, Reli; Ariani, Nurlina; Siregar , Sakinah Ubudiyah (PT ARRUS Intelektual Indonesia, 2025)
Time management is the achievement of the main goals of life as a result of setting aside meaningless activities that often take up a lot of time. Time management is a decision made by each person in managing time to achieve a planned goal. This research method uses descriptive analysis with a quantitative approach. The population in this study was The sample in this study was class IX-2 as a control class totaling 36 students and class IX-3 as an experimental class totaling 38 students. The data in this study were processed using the SPSS 24 Application with multiple linear regression tests. The results of the study showed that partially or T Test the Time Management and Problem Solving Ability variables had a positive and significant effect on the Creative Problem Solving (CPS) Learning Model Variable, this can be seen from the T count> T table with a sig value of 0.000 <0.05. While simultaneously or F Test had a positive and significant effect, this can be seen from the F count> F table with a sig value of 0.000 <0.05.